Cryosurgery of skin cancer – possibilities and limitations of the method – experiences of Dept. of Dermatology University School of Medical Sciences in Poznań - Kaźmierowski, Marek (Contemporary Oncology/Współczesna Onkologia, 1999)
The results of cryosurgery of 2748 skin cancers in 2316 patients after at least 3-year follow-up period were presented. Selection of patients for treatment and different cryosurgical methods were discussed. Reccurrences, mostly during the first 12 months, were seen in 2,9% treated lesions. The study have shown that cryosurgery is an effective method of treating selected skin cancers and produced excellent cosmetic results with cure rate comparable with other established methods of therapy.